2014
DOI: 10.3109/09546634.2014.946882
|View full text |Cite
|
Sign up to set email alerts
|

Saudi practical guidelines on biologic treatment of psoriasis

Abstract: The current treatment of psoriasis patients with biologic agents in the Kingdom of Saudi Arabia (KSA) is mainly based on clinical experience. Although there are published international guidelines for treatment with biologics, such as the European S3 guidelines (a joint project of the European Dermatology Forum, the European Academy of Dermatology and Venereology, and the International Psoriasis Council), many nations have found it beneficial to develop country-based guidelines that incorporate specific regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…The literature search returned a total of 145 publications and 10 of these described patients in Africa or the Middle East. Of these 10 publications, there were 4 research articles ( Table 1 ), 20 23 3 reviews ( Table 2 ), 8 , 24 , 25 2 guidelines (1 from South Africa in 2010 and 1 from Saudi Arabia in 2014; Table 3 ), 26 , 27 and 1 case study (published in Hebrew). 28 Two of the 4 research articles described non-interventional studies and 2 reported data from studies on the safety and efficacy of phototherapy (1 in patients with plaque psoriasis localized to the scalp or palmoplantar areas and 1 in patients ≥65 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…The literature search returned a total of 145 publications and 10 of these described patients in Africa or the Middle East. Of these 10 publications, there were 4 research articles ( Table 1 ), 20 23 3 reviews ( Table 2 ), 8 , 24 , 25 2 guidelines (1 from South Africa in 2010 and 1 from Saudi Arabia in 2014; Table 3 ), 26 , 27 and 1 case study (published in Hebrew). 28 Two of the 4 research articles described non-interventional studies and 2 reported data from studies on the safety and efficacy of phototherapy (1 in patients with plaque psoriasis localized to the scalp or palmoplantar areas and 1 in patients ≥65 years of age).…”
Section: Resultsmentioning
confidence: 99%
“…Until now, DR has mainly been described for TNFα inhibitors and ustekinumab [ 10 13 ]. The possibility of DR is only mentioned in a few guidelines [ 44 , 45 ]. To our knowledge, the current study is the first randomized, controlled trial designed to investigate disease activity-guided DR of IL-17i and IL-23i for psoriasis patients with low disease activity in a multicentric and pragmatic setting.…”
Section: Discussionmentioning
confidence: 99%
“…Research on the quality of life of psoriasis patients has also been the concern of some previous researchers, including research on the quality of life of psoriasis patients in the Osmanabad region, India. The results showed that the quality of life was low and very disturbing in life compared to other healthy individuals [10]. Another study examined the quality of life in patients with psoriasis in tertiary care hospitals concluded that psoriasis is a chronic recurrent disease and has a significant negative impact to the quality of life of the patient [11].…”
Section: Based On Medical Record Data Of Haji Adam Malik General Hospmentioning
confidence: 99%